(untitled) (El Taco en la Brea, 2024)
The main hypothesis of this paper maintains that the political in Roberto Santoro’s writing is redefined and updated through play and laughter as devices from which to read and interpret dictatorial violence and leftist militancy. Far from simply denouncing or protesting, His poetry transgresses commonplaces or crystallized ways of approaching the historical-political reality of the 1970s, through black humor, irony and the rewriting of children’s games, rounds and popular songs. His last two publications during his lifetime —Poesía en general (1973) and No negociable (1975)— and poems that remained unpublished until the appearance of his Obra poética completa (2009) will be taken into account for the analysis. There one can see a processing of the repressive context and its effects on bodies and subjectivities that does not deny pain or anger, nor militant enthusiasm, but it does incorporate new tones and figures to the revolutionary imagination, such as jokes, calambur, dance or children’s rituals.